Assessing Corporate Influence on Dietary Advice. Issue 5 (September 2019) - Snow, Denise
Abstract : It is important to have healthy skepticism when reading dietary advice because sometimes the sponsors or supporters of the source of this dietary advice have close relationships with the food industry. Funding from sources related to the topic of research can be acceptable as long as the relationships, sources, amounts, and potential conflicts of interest are fully disclosed in a transparent and detailed manner prominently within the document offering the advice or reporting the research results. Our nutrition expert, Denise Snow, explains the controversy.